Programavimas šiuolaikiniame informatikos mokyme - Lipeikienė, Joana (Pedagogika (Vilnius, Lithuania), 2004)
The rapid changes of the computer science (CS) subject have a profound effect on computer science education, affecting both the content and pedagogy. International CS organisations renew recommendations to CS curricula from time to time. CC2001 (Computer Science Curriculum 200!) of the Association for Computing Machinery is the basis for the nearest future curricula of the subject. Technological changes have increased the importance of many curricular topics. One of the topics is object-oriented programming. The paper deals with the problems of teaching object-oriented programming and presents the results of investigations on pedagogical university students' point of view on the subject and on innovations of learning object programming.